The relation between autonomy support and music enjoyment in online learning for music undergraduates in the post-COVID-19 era - Zhang, Yan-Han; Zhao, Yue-Han; Luo, Yuan-Yu; Yang, Xiantong; Tan, Dawei (Frontiers in Psychology, 2022)
Music enjoyment is considered to predict music-related academic performance and career choice. Although relevant research in non-music fields has demonstrated the association between teachers’ autonomy support and students’ academic enjoyment, it remains unknown whether this association is valid in the music discipline. In addition, in the post-COVID-19 era, online education has become a common way of teaching and learning for music undergraduates. In the form of online learning, the mechanisms mediating teachers’ music autonomy support and students’ music academic enjoyment are also unknown. This study draws on Pekrun’s theory of achievement emotions and control values to explore the mediating role of attributions and values in the association between autonomous support and academic achievement. In this study, 270 undergraduates majoring in music eventually completed the online surveys. Results from structural equation modeling indicated that autonomy support positively predicted music enjoyment and that attributions (i.e., internal attribution and external attribution) and values (i.e., intrinsic value, attainment value, utility value) mediated the association between autonomy support and music enjoyment. The findings also provide insights into possible avenue for promoting music enjoyment emotion during online teaching in the post-COVID-19 era. Implications and limitations are discussed in the study.